2010
DOI: 10.1103/physreva.81.032315
|View full text |Cite
|
Sign up to set email alerts
|

Universal linear Bogoliubov transformations through one-way quantum computation

Abstract: We show explicitly how to realize an arbitrary linear unitary Bogoliubov (LUBO) transformation on a multimode quantum state through homodyne-based one-way quantum computation. Any LUBO transformation can be approximated by means of a fixed, finite-sized, sufficiently squeezed Gaussian cluster state that allows for the implementation of beam splitters (in form of three-mode connection gates) and general one-mode LUBO transformations. In particular, we demonstrate that a linear four-mode cluster state is a suffi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
106
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(106 citation statements)
references
References 23 publications
0
106
0
Order By: Relevance
“…Then, the second and, in general, third modes of the cluster state are measured on suitable quadratures, which depend on the computation that we want to perform and are determined with the recipe of Ref. [15]. These quadrature measurements on each mode can be equivalently described as a suitable rotation matrix D meas , followed by a measurement in the same quadrature on all the modes, say,p.…”
Section: Mbqc Error Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the second and, in general, third modes of the cluster state are measured on suitable quadratures, which depend on the computation that we want to perform and are determined with the recipe of Ref. [15]. These quadrature measurements on each mode can be equivalently described as a suitable rotation matrix D meas , followed by a measurement in the same quadrature on all the modes, say,p.…”
Section: Mbqc Error Reductionmentioning
confidence: 99%
“…This state has been shown to be a universal resource for gaussian single-mode quantum computation [15]. The input modes used to build the cluster state are assumed to possess realistic squeezing levels, such as those seen in the four-mode multimode state of Ref.…”
Section: Optimization Of Cluster Statesmentioning
confidence: 99%
“…Therefore, the probabilistic problems existing in most qubit information systems of single photons [4][5][6] can be overcome. It has been theoretically and experimentally demonstrated that one-mode linear unitary Bogoliubov (LUBO) transformations corresponding to Hamiltonians that are quadratic in quadrature amplitude and phase operators of quantized optical modes (qumodes) can be implemented using a four-mode linear cluster state [13,14]. At the same time, the Deutsch-Jozsa algorithm for CVQC has been proposed [15].…”
Section: Introductionmentioning
confidence: 99%
“…A half teleportation with a beam-splitter coupling corresponds to a squeezing gate [21,22]. Note that it can be eliminated by adding an additional coupling node at the edge of cluster states, by which full quantum teleportation with full Bell measurements is performed into the cluster state instead of half teleporation with half Bell measurement [17].…”
Section: Protocol For Tuneable Entangling Gates Via Cluster Gain mentioning
confidence: 99%
“…For example the fixed-strength entangling gate demonstrated in Ref. [10] cannot have its entanglement strength tuned, and therefore it cannot completely make use of the underlying structure of the cluster state [17].…”
Section: Introductionmentioning
confidence: 99%